Optimization of Green Energy Extraction: An Application of Cross-Flow Micro-Hydro Turbine - Yassin, A.; M. I., Shahidul; S. T., Syed Shazali; A. H., Ruduan; S. M. A., Liakbar; Al-Khalid, Othman; Hushairi, Zen; A., Baharun (ENCON 2013, 2013)
This research attempts to optimize kinetic energy extraction from in-stream water for modelling a reliable and sustainable green energy source. Based on simulations and laboratory scale turbine testing, a prototype cross flow micro hydro turbine has been developed and tested. Test report indicates that developed turbine started to extract energy at 0.3 m/s water velocity; and maximum energy extraction was attained at 2.5 m/s which contributed to produce 132 RPM turbine speed. Energy extraction efficiency of the newly developed turbine was 51.5% at water velocity of 2.5 m/s velocity drop 35% at blades surface. Study concludes that these findings would be greatly useful in future research for developing commercially feasible micro hydro turbine.